2022
DOI: 10.1007/s12094-022-02830-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic viral vectors in the era of diversified cancer therapy: from preclinical to clinical

Abstract: With the in-depth research and wide application of immunotherapy recently, new therapies based on oncolytic viruses are expected to create new prospects for cancer treatment via eliminating the suppression of the immune system by tumors. Currently, an increasing number of viruses are developed and engineered, and various virus vectors based on effectively stimulating human immune system to kill tumor cells have been approved for clinical treatment. Although the virus can retard the proliferation of tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 143 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…162 Reovirus has a targeted lytic effect on cells activated by the RAS pathway, such as malignant gliomas cells and breast cancer cells. 163 Clinical trials and preclinical studies of Reovirus have shown great promise. 164 H-1 parvovirus (H-1PV) is a self-propagating virus with oncolytic and tumor-suppressing activity and is nonpathogenic in humans.…”
Section: Modification Of Ovsmentioning
confidence: 99%
See 1 more Smart Citation
“…162 Reovirus has a targeted lytic effect on cells activated by the RAS pathway, such as malignant gliomas cells and breast cancer cells. 163 Clinical trials and preclinical studies of Reovirus have shown great promise. 164 H-1 parvovirus (H-1PV) is a self-propagating virus with oncolytic and tumor-suppressing activity and is nonpathogenic in humans.…”
Section: Modification Of Ovsmentioning
confidence: 99%
“…Reovirus are nonenveloped virus with 9–12 linear double‐stranded RNA that occurs naturally in the mammalian respiratory and intestinal systems 162 . Reovirus has a targeted lytic effect on cells activated by the RAS pathway, such as malignant gliomas cells and breast cancer cells 163 . Clinical trials and preclinical studies of Reovirus have shown great promise 164 .…”
Section: Oncolytic Virotherapy For Brain Gliomamentioning
confidence: 99%
“…Some viruses, such as oncolytic viruses like the herpes simplex virus (HSV), not only act as delivery vectors for gene therapy but can also selectively infect and destroy tumor cells while simultaneously stimulating immune responses (Niemann & Kühnel, 2017). When HSV is used for oncolytic therapy, knocking out the main gene that HSV infects and replicates in normal cells can improve the targeting of HSVinfected tumor cells and enable them to selectively replicate in tumor cells (Tang et al, 2022). Besides, viral vectors are also being used in the development of vaccines.…”
Section: From Foes To Friendsmentioning
confidence: 99%
“…In Table 3 the combination studies of nanoparticles drug therapy with other effective therapies against RB are summarized. Finally, it is necessary to mention the last frontier of RB treatment which involved the use of oncolytic viral vectors that can be included in the nanomedicine approach [33,99,100].…”
Section: Future Perspectivementioning
confidence: 99%